2016
DOI: 10.1098/rspb.2015.1439
|View full text |Cite
|
Sign up to set email alerts
|

Irrational time allocation in decision-making

Abstract: Time is an extremely valuable resource but little is known about the efficiency of time allocation in decision-making. Empirical evidence suggests that in many ecologically relevant situations, decision difficulty and the relative reward from making a correct choice, compared to an incorrect one, are inversely linked, implying that it is optimal to use relatively less time for difficult choice problems. This applies, in particular, to value-based choices, in which the relative reward from choosing the higher v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 72 publications
(80 reference statements)
5
45
1
Order By: Relevance
“…According to this framework, decision difficulty, and in turn response time (RT), is proportional 48 to the relative difference in the evidence supporting each option, consistent with results from 49 perceptual (Ditterich et al, 2003) and value-based (Oud et al, 2016) decisions. 50…”
Section: Introduction 41supporting
confidence: 55%
“…According to this framework, decision difficulty, and in turn response time (RT), is proportional 48 to the relative difference in the evidence supporting each option, consistent with results from 49 perceptual (Ditterich et al, 2003) and value-based (Oud et al, 2016) decisions. 50…”
Section: Introduction 41supporting
confidence: 55%
“…While we were writing this paper, another group of researchers, independently, reported their results on two experiments similar to what we reported here Oud et al (2016). Specifically, in study 2 in that paper, participants performed a perceptual decision making task in which the hard and easy trials were presented randomly in blocks with fixed duration.…”
Section: Allocation Of Limited Time To Decisions With Different Outcomementioning
confidence: 55%
“…Previous research has identified a number of parallels between behavioral and neural patterns evoked by perceptual and value-based decisions [54][55][56] . Both have been well described by similar classes of evidence accumulation models 8,57,58 .…”
Section: Discussionmentioning
confidence: 99%